Early Postoperative Pain Control and Inflammation for Total Knee Arthroplasty: A Retrospective Comparison of Continuous Adductor Canal Block versus Single-Shot Adductor Canal Block Combined with Patient-Controlled Intravenous Analgesia - Xiaojuan Yang; Jun Dong; Wei Xiong; Fusen Huang (Emergency Medicine International)
Objective. The aim of this study was to compare pain control and inflammation among patients who received a continuous adductor canal block (CACB) versus single-shot adductor canal block (SACB) combined with patient-controlled intravenous analgesia (PCIA) for total knee arthroplasty (TKA) analgesia in the first two days after surgery. Design. Matched cohort retrospective study. Setting. University hospital. Patients. One hundred fifty-six patient charts were included in this study: 78 patients with CACB in Group A and 78 patients with SACB combined with PCIA in Group B. Patients were matched according to age, body mass index, and American Society of Anesthesiologists class. Measurements. The primary outcome of the study was Visual Analogue Scale (VAS) pain scores before operation (Pre) and at postoperative 6 (POH6), 12 (POH12), 24 (POH24), 30 (POH30), 36 (POH36), and 48 hours (POH48). Secondary outcomes included patient-controlled bolus, time of first postoperative ambulation, range of knee flexion and extension, inflammation cytokines on Pre and POH48, percentage of remedial analgesics treatment, incidence of adverse events and complications, hospital stay and cost, and Numerical Rating Scale (NRS) satisfaction scores at discharge. Main Results. Mean VAS scores at rest and with motion were lower in Group B than in Group A on all postoperative hours. At POH30, compared with Group A (1.1 ± 0.6), mean VAS scores at rest in Group B (0.9 ± 0.4) were lower (P=0.048), and compared with Group A (2.6 ± 0.7), mean VAS scores with motion in Group B (2.2 ± 0.8) were lower (P=0.001). The number of patient-controlled bolus was 4.3 ± 1.6 (95% CI 3.9–4.6) in Group A and 3.1 ± 1.3 (95% CI 2.8–3.4) in Group B, respectively (P<0.001). Patients in Group B displayed better functional recovery and inflammation results at POH48 than Group A with respect to range of knee flexion and extension (117.8 ± 10.9° vs. 125.2 ± 9.4°, P<0.001) and inflammation cytokines, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and interleukin-6 (IL-6) ((43.8 ± 16.1) vs. (36.8 ± 13.2), P=0.003; (34.9 ± 9.4 mg/L) vs. (29.6 ± 10.6 mg/L), P=0.001; (21.3 ± 8.7 pg/ml) vs. (14.0 ± 7.0 pg/ml), P<0.001)). Conclusion. SACB combined with PCIA in the first two days of patients undergoing TKA has better analgesic and beneficial effects on functional recovery and inflammation.